Prediction of drag and lift forces of a high-speed vessel at full scale by CFD-based GEOSIM method. (November 2022) - Can, Ugur; Bal, Sakir
In this study, it was aimed to obtain an accurate extrapolation method to compute lift and drag forces of high-speed vessels at full-scale by using CFD (Computational Fluid Dynamics) based GEOSIM (GEOmetrically SIMilar) method which is valid for both fully planing and semi-planing regimes. Athena R/V 5365 bare hull form with a skeg which is a semi-displacement type of high-speed vessel was selected with a model family for hydrodynamic analyses under captive and free to sinkage/trim conditions. Total drag and lift forces have been computed for a generated GEOSIM family of this form at three different model scales and full-scale for Fr =  0.8 by an unsteady RANS (Reynolds Averaged Navier–Stokes) solver. k –ε turbulence model was used to simulate the turbulent flow around the hulls, and both DFBI (Dynamic Fluid Body Interaction) and overset mesh technique were carried out to model the heave and pitch motions under free to sinkage/trim condition. The computational results of the model family were used to get "drag-lift ratio curve" for Athena hull at a fixed Fr number and so the corresponding results at full scale were predicted by extrapolating those of model scales in the form of a non-dimensional ratios of drag-lift forces. Then the extrapolated full-scale results calculated by modified GEOSIM method were compared with those of full-scale CFD and obtained by Froude extrapolation technique. The modified GEOSIM method has been found to be successful to compute the main forces (lift and drag) acting on high-speed vessels as a single coefficient at full scale. The method also works accurately both under fully and semi-planing conditions.